Hypothalamic Rax+ tanycytes contribute to tissue repair and tumorigenesis upon oncogene activation in mice - Wenhui Mu (Nature Portfolio, 2021)
Tanycytes contribute to the regulation of multiple hypothalamic functions. Here the authors investigate the regenerative and tumorigenic potential of adult Rax+ tanycytes in the median eminence in the context of the stem cell niche in mice.